A study of variations in the branching pattern of popliteal artery and its clinical perspective - Bettaiah, Anisha; Venkat, Sangeetha; G., Saraswathi (International Journal of Research in Medical Sciences, 2017)
Background: Popliteal artery is the continuation of femoral artery which is the main and prime arterial supply to the knee, leg and foot. Variations of popliteal artery have been the subject of repeated study as exposure of this artery is required in both emergency and elective vascular procedures. Knowledge of the anatomical variations in the branching of popliteal artery is important, because damage to artery and its branches can lead to limb disability or life threatening haemorrhage. Methods: A total of 40 popliteal arteries were studied by dissection method. Specimens were collected from the cadavers which were available in the department of anatomy, JSS medical college, Mysore, India. Results: The origin, course and termination of the popliteal artery in all the 40 specimens were normal. Regarding the branching pattern of genicular arteries, there was a common stem of origin for superior medial genicular artery (SMGA), middle genicular artery (MGA), superior lateral genicular artery (SLGA) in 2 specimens (5%). Conclusions: Popliteal artery is the commonly approached site for above and below knee bypass grafts. It is also frequently injured during penetrating and blunt trauma involving lower extremity. Although prevalence of the variations was less in our study, the awareness of possible variations will be beneficial to angiographers and to vascular surgeons and orthopaedic surgeons.